Negative pole piece with multilayer structure, preparation method of negative pole piece and lithium ion battery
By using multi-layer structure negative electrode sheets in lithium-ion batteries, multi-string coating is used to form a layer of soluble polymer material and dissolve it in the electrolyte to build an ion channel, and electron transmission of graphite negative electrode materials under fast charging conditions is solved. Low rates and laser etching residue issues improve battery performance and safety.
Patent Information
- Application Number
- CN202411335741.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-03
AI Technical Summary
The graphite negative electrode material has a low electron transfer rate under fast charging conditions in lithium-ion batteries, resulting in a decrease in the ion transfer rate, and the residual negative electrode powder after laser etching leads to self-discharge and safety risks.
Using a multi-layer structure negative electrode sheet, including a negative electrode current collector, a first active layer, a composite layer and a second active layer, the composite layer forms a soluble polymer material layer through a multi-string coating method, and dissolves it in the electrolyte to construct Ion channel, eliminating the laser etching groove process.
It improves the ion transmission performance of lithium-ion batteries, avoids negative electrode powder residues, reduces safety risks, shortens production cycles, and improves the utilization rate of negative electrode sheets.
Smart Images

Figure CN119252857A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a multi-layered negative electrode sheet and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Graphite negative electrode material is an important commercial battery material, mainly used in lithium-ion batteries. Graphite negative electrode material has poor transmission kinetics under fast charging conditions. In order to pursue high electron transfer rate, the coating thickness of graphite negative electrode material is usually increased, but this also brings about a decrease in ion transfer rate. Moreover, due to the lithium-phobic nature of the graphite surface, thick graphite electrodes will further lead to an increase in ion transfer resistance, thereby affecting battery performance and limiting the fast charging application of graphite negative electrode materials in the field of lithium-ion batteries.
[0003] To address the above issues, the industry currently uses laser to etch grooves with uniform spacing on the surface of the negative electrode plate, uses the grooves to widen the spacing between graphite layers, and constructs additional ion transmission channels to meet the fast charging needs of lithium batteries; however, in this method, the negative electrode powder left after the laser etching process cannot be effectively removed; after being made into a finished battery, the negative electrode powder will cause a tiny self-discharge inside the battery, which is not conducive to the long-term storage of the battery, and once the self-discharge is too fast, it will also cause the battery to bulge, posing a safety risk. Summary of the invention
[0004] In view of the above problems existing in the prior art, the object of the present invention is to provide a multi-layer structure negative electrode sheet and a preparation method thereof and a lithium ion battery.
[0005] To achieve the above object, the present invention adopts the following technical solutions:
[0006] The present invention provides a multi-layer structured negative electrode sheet, comprising a negative electrode current collector and a first active layer, a composite layer and a second active layer sequentially stacked on one side of the negative electrode current collector; the composite layer comprises a soluble polymer material layer obtained by a multi-striped coating method, and a third active layer filling the gaps in the soluble polymer material layer.
[0007] In some embodiments, the slurry used in the soluble polymer material layer includes any one of water-based polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; the polymer molecular weight used in the soluble polymer material layer is 3000-50000, and / or the melting point is 50°C-80°C.
[0008] In some embodiments, the composite layer is provided with multiple layers; each of the composite layers covers the outer surface of the first active layer or the second active layer, and the outer surface of each of the composite layers is covered with the second active layer; the thickness of the soluble polymer material layer is 1 / 10 to 3 / 10 of the total thickness of the coating layer of the multi-layer structure negative electrode sheet.
[0009] In some embodiments, the multi-striped coating method has a coating spacing of 0.5 mm to 5 mm, and / or 0.01 mm. 2 ~0.1mm 2 The soluble polymer material layer is applied on a coating cross-sectional area of
[0010] In some embodiments, the soluble polymer material layer is coated with a coating interval of 0.5 mm to 3 mm.
[0011] In some embodiments, the coating cross-sectional area of the soluble polymer material layer is denoted as S, the molecular weight of the polymer used in the soluble polymer material layer is denoted as M, 4≤(S / M)*10 7 ≤67.
[0012] The present invention further provides a method for preparing a multi-layer structured negative electrode sheet, comprising the following steps:
[0013] S1, coating the negative electrode slurry on the surface of the negative electrode current collector and curing it to form a first active layer;
[0014] S2, coating the surface of the first active layer with negative electrode slurry and polymer slurry and curing to obtain a composite layer; in the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a soluble polymer material layer, and the negative electrode slurry forms a third active layer to fill the gaps in the soluble polymer material layer;
[0015] S3, coating the negative electrode slurry on the surface of the composite layer and curing it to form a second active layer.
[0016] In some embodiments, step S2 includes:
[0017] Coating the polymer slurry on the surface of the first active layer by multi-striped coating and curing to form the soluble polymer material layer;
[0018] Applying negative electrode slurry in the gaps of the soluble polymer material layer to fill and solidify to obtain a third active layer, wherein the soluble polymer material layer and the third active layer form the composite layer;
[0019] or;
[0020] Coating the negative electrode slurry on the surface of the first active layer by a multi-striped coating method and curing the negative electrode slurry to obtain the third active layer;
[0021] Applying the polymer slurry in the gaps of the third active layer to fill and solidify to obtain the soluble polymer material layer, wherein the soluble polymer material layer and the third active layer form the composite layer;
[0022] or;
[0023] The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head at the same time and then cured to obtain the composite layer.
[0024] In some embodiments, the polymer slurry is any one of waterborne polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; the polymer molecular weight used in the polymer slurry is 3000-50000, and / or the melting point is 50°C-80°C.
[0025] In some embodiments, step S2 further includes:
[0026] The cross-sectional area of 0.01 mm is intermittently coated on the surface of the pole piece in a multi-strip coating manner according to a coating interval of 0.5 mm to 5 mm. 2 ~0.1mm 2 A layer of dissolvable polymer material.
[0027] In some embodiments, the mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml.
[0028] In some embodiments, it also includes:
[0029] S4, repeating the operations in steps S2 and S3 to obtain the multi-layer structured negative electrode sheet;
[0030] In the multi-layer structured negative electrode sheet, the thickness of the soluble polymer material layer is 1 / 10 to 3 / 10 of the total thickness of the coating layers of the multi-layer structured negative electrode sheet.
[0031] In some embodiments, the curing is ultraviolet light curing or baking curing;
[0032] During the UV curing, the intensity of the UV light is 900 mW / cm 2 ~1100mW / cm 2 , and / or the curing power is 30% to 50%, and / or the curing time is 5s to 15s;
[0033] During the drying and curing, the negative electrode current collector is dried in an oven at 40° C. to 50° C.
[0034] The present invention further provides a lithium-ion battery, comprising the above-mentioned multi-layer structured negative electrode sheet, and also comprising a positive electrode sheet, a separator and an electrolyte;
[0035] The electrolyte includes a lithium salt and an organic solvent; wherein the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] First, the present invention introduces a soluble polymer material layer into the coating layer of the negative electrode plate. When the negative electrode plate is manufactured into a finished battery, it will be immersed in an electrolyte. The electrolyte contains a large amount of organic solvents for dissolving lithium salts. A polymer with a chemical structure similar to these solvents and soluble in these solvents is selected as the soluble polymer material layer, so that the soluble polymer material layer can be dissolved in the electrolyte, thereby constructing a channel in the coating layer; the present invention utilizes the physical miscibility between the organic solvent and the polymer slurry in the electrolyte, and when the negative electrode plate is manufactured into a finished battery, a plurality of grooves can be dissolved in the coating layer of the negative electrode plate, thereby constructing ion channels to accelerate ion transmission performance; the battery manufactured by the present invention can save the process of constructing grooves before the plate assembly, thereby shortening the production cycle;
[0038] Secondly, in the composite layer of the present invention, gaps are left between the multiple soluble polymer material layers obtained by stripe coating, and the gaps are filled with active substances of negative electrode materials, so that the active substances and the polymer slurry are arranged in an alternating manner; the composite layer is located between the two active layers to form a multilayer structure of active layer-composite layer-active layer; compared with the traditional method of laser etching grooves on the surface of the electrode piece, the multilayer grooves inside the slurry layer can improve the utilization rate of the negative electrode electrode piece to a greater extent, not only providing a fast channel for lithium ions in the length direction of the electrode piece, but also shortening the ion migration path of the upper and lower active layers; there will be no negative electrode powder residue inside the lithium ion battery prepared by the present invention, and the polymer material is dissolved in the electrolyte to form a stable solution, which has no adverse effect on the working performance of the battery and effectively reduces the safety risk. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 It is a schematic diagram of the cross-sectional structure of the coating layer of the multi-layer structure negative electrode sheet of the present invention;
[0040] In the figure: 10, negative electrode current collector; 20, first active layer; 30, composite layer; 301, soluble polymer material layer; 302, third active layer; 40, second active layer. DETAILED DESCRIPTION
[0041] To make the technical solutions and advantages of the present invention more clear, the present invention and its beneficial effects will be further described in detail below in conjunction with specific implementation methods, but the implementation methods of the present invention are not limited thereto.
[0042] See also Figure 1 , Figure 1 It is a schematic diagram of the cross-sectional structure of the coating layer of the multi-layer structure negative electrode plate of the present invention; the multi-layer structure negative electrode plate provided by the present invention includes a negative electrode collector 10 and a first active layer 20, a composite layer 30 and a second active layer 40 stacked in sequence on one side of the negative electrode collector 10; the composite layer 30 includes a soluble polymer material layer 301 obtained by a multi-striped coating method, and a third active layer 302 filling the gaps in the soluble polymer material layer 301.
[0043] In this solution, the first active layer 20, the second active layer 40 and the third active layer 302 are all coated with the same negative electrode active slurry; the composite layer 30 in the multi-layer structure negative electrode plate is located between the two active layers, forming a multi-layer structure of active layer-composite layer-active layer. When the negative electrode plate is made into a finished battery, it will be immersed in the electrolyte. Since the organic solvent in the electrolyte is physically compatible with the polymer in the soluble polymer material layer 301, the soluble polymer material layer 301 will dissolve in the electrolyte, thereby constructing a groove in the composite layer 30 to provide a fast channel for lithium ions; and this multi-layer structure of active layer-composite layer-active layer can also shorten the ion migration path of the upper and lower active layers, reduce the battery impedance, and further improve the utilization rate of the negative electrode plate.
[0044] Furthermore, the slurry used in the soluble polymer material layer 301 includes any one of waterborne polyurethane (PU), polyethylene oxidized (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), and polyvinylidenedifluoride (PVDF); the molecular weight of the polymer used in the soluble polymer material layer 301 is 3000 to 50000, and / or the melting point is 50°C to 80°C.
[0045] Furthermore, the composite layer 30 is provided with multiple layers; each composite layer 30 covers the outer surface of the first active layer 20 or the second active layer 40, and the outer surface of each composite layer 30 is covered with the second active layer 40; the thickness of the soluble polymer material layer 301 is 1 / 10 to 3 / 10 of the total thickness of the coating layer of the multi-layer structure negative electrode plate; each composite layer 30 is arranged between the two active layers, and the composite layer 30 and the active layer coated on the outer surface of the composite layer 30 are regarded as a unit. Increasing the number of composite layers 30 also increases the number of units. By controlling the number of units, multiple layers of grooves can appear in the slurry layer, and each layer of grooves is arranged between the two active layers, thereby accelerating the ion transfer in the two active layers and further improving the fast charging performance of the battery.
[0046] Furthermore, in the multi-striped coating method, the coating spacing is 0.5 mm to 5 mm, and / or 0.01 mm. 2 ~0.1mm 2 The soluble polymer material layer 301 is applied on a coating cross-sectional area.
[0047] Furthermore, the soluble polymer material layer 301 is coated at a coating interval of 0.5 mm to 3 mm.
[0048] Furthermore, the coating cross-sectional area of the soluble polymer material layer is denoted as S, the molecular weight of the polymer used in the soluble polymer material layer is denoted as M, 4≤(S / M)*10 7 ≤67.
[0049] The preparation method of the multi-layer structure negative electrode sheet is as follows:
[0050] S1, coating the negative electrode slurry on the surface of the negative electrode current collector and curing it to form a first active layer;
[0051] S2, coating the negative electrode slurry and the polymer slurry on the surface of the first active layer and curing them to obtain a composite layer; in the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a soluble polymer material layer, and the negative electrode slurry forms a third active layer to fill the gaps in the soluble polymer material layer;
[0052] S3, coating the negative electrode slurry on the surface of the composite layer and curing it to form a second active layer.
[0053] Further, step S2 includes:
[0054] A polymer slurry is coated on the surface of the first active layer by a multi-striped coating method and solidified to form a soluble polymer material layer;
[0055] Applying negative electrode slurry in the gap of the soluble polymer material layer to fill and solidify to obtain a third active layer, and the soluble polymer material layer and the third active layer form a composite layer;
[0056] or;
[0057] A third active layer is obtained by coating the negative electrode slurry on the surface of the first active layer by a multi-striped coating method and curing the negative electrode slurry.
[0058] Applying polymer slurry in the gaps of the third active layer to fill and solidify to obtain a soluble polymer material layer, wherein the soluble polymer material layer and the third active layer form a composite layer;
[0059] or;
[0060] The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head and then cured to obtain a composite layer.
[0061] The coating of the composite layer in the present invention includes three schemes, namely: first coating the polymer slurry and then coating the negative electrode slurry, or first coating the negative electrode slurry and then coating the polymer slurry, or coating the polymer slurry and the negative electrode slurry at the same time; among them, the scheme of first coating the polymer slurry and curing it, and then coating the negative electrode slurry and curing it has the best effect; because under such operation, the integrity of the pre-coating layer formed by the polymer slurry can be guaranteed as much as possible, and the possibility of the negative electrode slurry and the polymer slurry flowing with each other during coating and causing the interface between the two to be blurred is greatly reduced; each time after coating the polymer slurry or the negative electrode slurry, a curing step must be performed to avoid mixing of the negative electrode slurry and the polymer slurry during subsequent coating.
[0062] Furthermore, the mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml; the selection of the mass concentration of the polymer slurry is crucial. If the mass concentration is too low, it will affect the coating effect and curing degree of the polymer slurry, and if the mass concentration is too high, the slurry will have poor fluidity; selecting a polymer slurry with a mass concentration of 10 mg / ml to 50 mg / ml can achieve better coating and curing effects of the polymer slurry while ensuring fluidity.
[0063] Furthermore, it also includes:
[0064] S4, repeating the operations in steps S2 and S3 to obtain a multi-layer structured negative electrode sheet;
[0065] In the multi-layer structured negative electrode sheet, the thickness of the soluble polymer material layer is 1 / 10 to 3 / 10 of the total thickness of the coating layer of the multi-layer structured negative electrode sheet; each time a composite layer is added, step S5 is repeated.
[0066] Further, the curing is ultraviolet light curing or baking curing;
[0067] During UV curing, the intensity of UV light is 900mW / cm 2 ~1100mW / cm 2, and / or the curing power is 30% to 50%, and / or the curing time is 5s to 15s;
[0068] During drying and curing, the negative electrode current collector is dried in an oven at 40°C to 50°C;
[0069] Preferably, the polymer slurry is cured by ultraviolet light, and the negative electrode slurry is cured by drying; this is because the polymer slurry is easier to shape when cured by ultraviolet light, and the time required for the negative electrode slurry to be completely cured by drying is shorter than the time required by ultraviolet light.
[0070] Example 1
[0071] This embodiment 1 provides a multi-layer structured negative electrode sheet and a lithium-ion battery including the negative electrode sheet, wherein:
[0072] 1. Preparation of negative electrode sheet:
[0073] (1) preparing 20 mg / ml of water-based polyurethane (PU) slurry with a molecular weight of 10,000; mixing graphite, carboxymethyl cellulose and a binder in a mass ratio of 97.7:1.1:1.2 to obtain a negative electrode slurry; coating a layer of the negative electrode slurry on the surface of a copper foil, and drying the layer in an oven at 45° C. to obtain a first active layer on the surface of the copper foil;
[0074] (2) On the surface of the dried electrode, use stripe coating to coat the cross-sectional area of 0.02 mm at an interval of 1.5 mm. 2 PU slurry, UV light curing molding, the intensity of UV light is 1100mW / cm 2 , the curing power is 40%, the curing time is 10s, and a PU slurry layer is obtained on the surface of the first active layer;
[0075] (3) The negative electrode slurry is coated in the blank stripe area of the PU slurry layer, that is, in the gap of the PU slurry layer, by stripe coating to fill it, and then dried in an oven at 45°C to obtain a third active layer; the third active layer and the PU slurry layer form a composite layer; the coating thickness of the third active layer is equal to the coating thickness of the PU slurry layer, and the third active layer shall not cover the PU slurry layer during coating;
[0076] (4) coating a layer of negative electrode slurry on the surface of the dried composite layer and drying it in an oven at 45° C. to obtain a second active layer;
[0077] (5) Repeat the operations in steps (2), (3) and (4);
[0078] (6) drying the electrode sheet at 60° C., and then cold pressing and slitting to obtain a multi-layer structured negative electrode sheet, which is kept for later use;
[0079] The negative electrode plate obtained in this embodiment 1 has a five-layer structure of active layer-composite layer-active layer-composite layer-active layer; in this negative electrode plate, the single-layer coating thickness of the PU slurry is 2 / 10 of the total coating thickness of the negative electrode plate, and the single-layer coating thickness of the PU slurry is equal each time.
[0080] 2. Preparation of positive electrode sheet:
[0081] The lithium iron phosphate, the conductive agent and the binder are uniformly mixed in a mass ratio of 97:1.5:1.5 to prepare a positive electrode slurry; wherein the conductive agent is conductive carbon black and the binder is PVDF;
[0082] The positive electrode slurry is coated on aluminum foil, dried at 85°C, and then cold pressed, cut into strips, and stored for later use.
[0083] 3. Preparation of diaphragm:
[0084] The PE-based film is coated with aluminum oxide / PVDF slurry on both sides, and after drying, it is cut into strips and kept for later use.
[0085] 4. Preparation of electrolyte:
[0086] Lithium hexafluorophosphate (LiPF6) is dissolved in a mixed solvent of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) to obtain an electrolyte with a concentration of 1 mol / L; the mass ratio of EC, DMC and EMC in the mixed solvent is 1:2:1.
[0087] 5. Preparation of lithium-ion batteries:
[0088] The negative electrode sheet, positive electrode sheet, separator and electrolyte obtained in the above steps are combined to prepare a soft-pack lithium-ion battery, which is left to stand at room temperature for 24 hours and at high temperature for 16 hours before use;
[0089] After the lithium-ion battery is prepared, it is left to stand for a period of time, which can accelerate the electrolyte's full infiltration of the negative and positive electrodes to form good electrical contact; it can also activate the electrode materials and balance the chemical reactions inside the battery; high-temperature standing is also to evaluate the battery's safety performance and observe whether it will experience abnormal phenomena such as overheating and leakage; it also provides time for the electrolyte to fully dissolve the PU slurry layer and form grooves in the composite layer.
[0090] Example 2-3
[0091] Specifically, embodiments 2-3 all provide a multi-layer structured negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0092] The only difference between Example 2 and Example 1 is that the coating spacing of the PU slurry is 0.5 mm;
[0093] The only difference between Example 3 and Example 1 is that the coating spacing of the PU slurry is 3 mm.
[0094] Embodiment 4-5
[0095] Specifically, embodiments 4-5 all provide a multi-layer structured negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0096] The only difference between Example 4 and Example 1 is that the coating cross-sectional area of the PU slurry is 0.01 mm 2 ;
[0097] The only difference between Example 5 and Example 1 is that the coating cross-sectional area of the PU slurry is 0.06 mm 2 .
[0098] Example 6
[0099] This embodiment 6 provides a multi-layer structured negative electrode sheet and a lithium ion battery including the negative electrode sheet; specifically, the difference between embodiment 6 and embodiment 1 is only that:
[0100] In this embodiment 6, step (5) in embodiment 1 is not executed, and step (6) is directly entered after the operation of step (4) is executed; the multilayer structure negative electrode plate obtained in this embodiment 6 has a three-layer structure of active layer-composite layer-active layer, and the total coating thickness in the multilayer structure negative electrode plate obtained in this embodiment 6 is equal to the total coating thickness in the negative electrode plate in embodiment 1.
[0101] Embodiment 7-8
[0102] Specifically, embodiments 7-8 all provide a multi-layer structured negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0103] The only difference between Example 7 and Example 1 is that the single-layer coating thickness of the PU slurry is 1 / 10 of the total coating thickness of the negative electrode plate;
[0104] The only difference between Example 8 and Example 1 is that the single-layer coating thickness of the PU slurry is 3 / 10 of the total coating thickness of the negative electrode plate;
[0105] Examples 9-10
[0106] Specifically, embodiments 9-10 all provide a multi-layer structured negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0107] The only difference between Example 9 and Example 1 is that the molecular weight of the polymer in the coated PU slurry is 5000.
[0108] The only difference between Example 10 and Example 1 is that the molecular weight of the polymer in the coated PU slurry is 15,000.
[0109] Embodiment 11
[0110] Specifically, this embodiment 11 provides a multi-layer structured negative electrode sheet and a lithium-ion battery including the negative electrode sheet;
[0111] The only difference between Example 11 and Example 1 is that the 20 mg / ml PU slurry in Example 1 is replaced by 20 mg / ml PEO slurry.
[0112] Comparative Example 1
[0113] This comparative example 1 provides a negative electrode sheet and a lithium ion battery including the negative electrode sheet. Specifically, the difference between comparative example 1 and embodiment 1 is that:
[0114] In this comparative example 1, steps (4) and (5) in Example 1 are not performed, and step (6) is directly performed after step (3) is performed; the multilayer structure negative electrode sheet obtained in this comparative example 1 has a two-layer structure of active layer-composite layer.
[0115] Comparative Example 2
[0116] This comparative example 2 provides a negative electrode plate and a lithium ion battery including the negative electrode plate. Specifically, the difference between comparative example 2 and example 1 is only that:
[0117] In this comparative example 2, the 20 mg / ml PU slurry prepared in Example 1 and the negative electrode slurry are mixed in a mass ratio of 1:1 to obtain a mixed slurry. A layer of the mixed slurry is coated on the surface of the copper foil and then dried at 60°C. The dried electrode sheet is cold pressed and stripped to obtain a multi-layer structure negative electrode sheet, which is retained for later use; wherein the coating thickness of the mixed slurry is equal to the total thickness of the coating layer of the multi-layer structure negative electrode sheet in Example 1.
[0118] Comparative Examples 3-4
[0119] Specifically, Comparative Examples 3-4 all provide a negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0120] The difference between Comparative Example 3 and Example 1 is that the coating cross-sectional area of the PU slurry is 0.002 mm 2 ;
[0121] The difference between Comparative Example 4 and Example 1 is that the coating cross-sectional area of the PU slurry is 0.2 mm 2 .
[0122] Comparative Examples 5-6
[0123] Specifically, Comparative Examples 5-6 all provide a negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0124] The difference between Comparative Example 5 and Example 1 is that the single-layer coating thickness of the PU slurry is 1 / 20 of the total coating thickness of the negative electrode plate;
[0125] The only difference between Comparative Example 6 and Example 1 is that the single-layer coating thickness of the PU slurry is 4 / 10 of the total coating thickness of the negative electrode plate;
[0126] Comparative Examples 7-8
[0127] Specifically, Comparative Examples 7-8 all provide a negative electrode sheet and a lithium ion battery comprising the negative electrode sheet;
[0128] The only difference between Comparative Example 7 and Example 1 is that the molecular weight of the polymer in the coated PU slurry is 1000.
[0129] The only difference between Comparative Example 8 and Example 1 is that the molecular weight of the polymer in the coated PU slurry is 100,000.
[0130] Comparative Example 9
[0131] Specifically, Comparative Example 9 provides a negative electrode sheet and a lithium ion battery including the negative electrode sheet;
[0132] The difference between Comparative Example 9 and Example 1 is that the molecular weight of the polymer in the coated PU slurry is 10000 and the coating cross-sectional area is 0.08 mm 2 .
[0133] Test Case
[0134] The lithium ion batteries obtained in Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to the following operations:
[0135] Cyclic capacity test: In the voltage range of 2.5-4.2V, the battery test system of Newwell Electronics Co., Ltd. was used to perform charge and discharge tests on various lithium-ion battery samples at rates of 0.2C, 0.5C, 1C, 3C, and 5C. The test results are shown in Table 2. The test also included 600 charge and discharge cycles at a constant current density of 3C. The test results are shown in Table 1.
[0136] Table 1. Specific capacity test results of 600 cycles at 3C rate
[0137]
[0138]
[0139] Table 2. Cycle specific capacity test results at different rates
[0140] sample 0.2C 0.5C 1C 3C 5C Example 1 169.1 154.4 138.7 127.3 114.9 Comparative Example 1 168.1 152.4 134.7 121.3 107.9 Comparative Example 2 163.7 149.6 129.4 118.3 93.2
[0141] Battery impedance test: The conventional method was used to perform impedance tests on the batteries prepared in the examples and comparative examples. The test results are shown in Table 3, where S is the coating cross-sectional area of the PU slurry, and M is the molecular weight of the polymer in the PU slurry.
[0142] Table 3. Battery impedance test results
[0143]
[0144] First, by observing the test results of Examples 1 to 3 in Tables 1 and 3, it can be seen that the discharge specific capacity of the battery in Examples 2 and 3 is slightly lower than the discharge specific capacity of the battery in Example 1, indicating that when the coating spacing of the polymer slurry is too large or too small, the diffusion resistance of lithium ions will increase, which is not conducive to the improvement of the fast charging performance of the battery; specifically, when the coating spacing of the PU slurry in the stripe coating is too narrow, it will not only pose certain challenges to the coating process, but also easily cause the two adjacent polymer slurries to contact or even overlap, thereby affecting the subsequent coating and rolling effects, resulting in a decrease in the performance of the lithium ion battery; in addition, the constructed groove spacing does not meet the requirements and cannot play a role in accelerating ion transmission; and when the coating spacing of the PU slurry in the stripe coating is too wide, the number of ion channels constructed on the electrode sheet is insufficient, and the surface density of the negative electrode sheet slurry is insufficient, which will also lead to a decrease in the cycle performance of the lithium ion battery; when the coating spacing of the polymer slurry in Example 1 of the present invention is controlled at 1.5 mm, the rate performance of the lithium ion battery can be better improved.
[0145] Secondly, it can be seen from the test results of Example 1, Example 4, Example 5, Comparative Example 3 and Comparative Example 4 in Table 1 and Table 3 that when the coating cross-sectional area of the PU slurry in the stripe coating is too large or too small, it will also have a certain impact on the impedance and discharge specific capacity of the lithium-ion battery; specifically, the coating cross-sectional area of the PU slurry is the cross-sectional area of the groove formed after the soluble polymer material layer is dissolved; if the coating cross-sectional area of the PU slurry is too small, the constructed groove space is insufficient, it is difficult to establish a large number of ion channels on the electrode, and it will affect the battery's liquid retention ability and liquid retention consistency. The reduction in liquid retention consistency is mainly due to the fact that the battery has a large amount of ion channels and a large amount of ion channels. This is because the amount of PU slurry used is reduced, and the interaction ability between the electrolyte and the PU slurry is also reduced; when the coating cross-sectional area of the PU slurry is too large, the cross-sectional area of the constructed groove is large, and the space in the groove that can accommodate and store the electrolyte is large, and its liquid retention capacity will increase; but the increase in the coating cross-sectional area of the PU slurry also means an increase in the amount of PU slurry used, and the ability of the electrolyte to dissolve PU will be weakened as the amount of PU slurry used increases, which may make the groove construction depth insufficient or difficult to form, thereby resulting in a decrease in its liquid retention consistency; in Example 1 of the present invention, the coating cross-sectional area of the polymer slurry is controlled at 0.01mm 2 ~0.1mm 2 When the battery is heated, it can achieve better liquid retention capacity and consistency.
[0146] In addition, by observing the test results of Example 1 and Example 6 in Table 1 and Table 3, it can be seen that the battery assembled with the negative electrode sheet having a five-layer structure of active layer-composite layer-active layer-composite layer-active layer in Example 1 has a higher discharge specific capacity and lower impedance than the battery assembled with the negative electrode sheet having a three-layer structure of active layer-composite layer-active layer in Example 6; it can be seen that by providing more composite layers in the coating layer of the negative electrode sheet, a larger number of grooves with denser distribution will be constructed when the electrolyte dissolves the soluble polymer material layer, which helps to provide more additional transmission channels for lithium ions, and can further effectively improve the rate performance of lithium-ion batteries.
[0147] Furthermore, by observing the test results of Example 1 and Comparative Example 1 in Tables 1 to 3, it can be seen that after 600 cycles at a 3C rate, the discharge specific capacity of the lithium-ion battery in Example 1 is 7.2 mAh / g higher than that in Comparative Example 1, and the battery impedance in Example 1 is 1.5 mΩ lower than that in Comparative Example 1; the negative electrode plate in Comparative Example 1 has a two-layer structure of an active layer-composite layer, and compared with the negative electrode plate in Comparative Example 1 in which only grooves are formed on the surface of the active layer by physical dissolution of PU by the electrolyte, the negative electrode plate in Example 1 has a five-layer structure of an active layer-composite layer-active layer-composite layer-active layer, and a double-layer groove can be constructed inside the coating layer to provide more ion transmission channels for lithium ions, effectively improving the overall utilization rate of the negative electrode plate, reducing the battery impedance, and thus improving the battery's cycle performance and charging rate.
[0148] Furthermore, after the polymer slurry and the negative electrode slurry of equal mass are mixed and coated on the current collector to obtain a mixed slurry layer, since the organic solvent used in the electrolyte has a certain miscibility with the polymer slurry, the polymer slurry will construct irregularly shaped channels in the mixed slurry layer after being dissolved in the electrolyte; observing the test results of Example 1 and Comparative Example 2 in Table 1 and Table 3, it can be seen that the irregular channels constructed in the mixed slurry layer can indeed reduce the diffusion resistance of lithium ions to a certain extent, but the effect on improving the rate charging of lithium-ion batteries is not obvious.
[0149] Further, by observing the test results of Example 1 and Example 11 in Table 1, it can be seen that after the PU slurry is replaced with PEO slurry in Example 11, compared with Example 1, the initial discharge specific capacity of the obtained battery is reduced by 13.9 mAh / g, and the discharge specific capacity after 600 cycles is also reduced by 15.1 mAh / g; this is mainly because PU has a two-phase structure, and the two-phase structure of PU includes a soft segment and a hard segment, wherein the molecular soft segment composed of polyether can be solvated with the lithium salt in the electrolyte, promote ion transport, and improve the electrolyte ion conductivity, thereby improving the cycle performance of the battery; and the molecular hard segment formed by polar groups such as carbamate can produce physical crosslinking points and construct a three-dimensional network structure, so that PU has good SEI film-forming properties (Solid Electrolyte Interface membrane, SEI); SEI membrane is an interface membrane located between the electrode and the electrolyte in a lithium ion battery. The stability of the SEI membrane has an important influence on the overall performance and service life of the battery. The use of PU can help further maintain the stability and safety performance of the battery and provide a guarantee for improving the capacity attenuation of a long cycle.
[0150] Furthermore, by observing the test results of Example 1, Example 9, Example 10, Comparative Example 7 and Comparative Example 8 in Table 1, it can be seen that the molecular weight of PU in the PU slurry will also affect the liquid retention consistency of the battery; when the molecular weight of PU is too small, as M decreases, the fluctuation range of the battery's liquid retention capacity is small, but its liquid retention consistency decreases. This is mainly because the decrease in the molecular weight of PU directly affects the solvation between the polymer and the salt in the electrolyte; when the molecular weight of PU is too large, as M increases, the battery's liquid retention capacity and liquid retention consistency both show a downward trend. This is mainly because the increase in the molecular weight of PU exacerbates the dissolution of the electrolyte. difficulty, resulting in incomplete dissolution of the polymer in the groove, affecting the battery's liquid retention capacity and liquid retention consistency, thereby affecting the battery performance; in addition, observing the impedance values of Example 1 and Example 9 in Table 3, it is found that Example 9 has a higher impedance than Example 1; this is because PU has a two-phase structure, and the molecular soft segment composed of polyether can be solvated with the salt in the electrolyte, promoting ion transport, improving the electrolyte ion conductivity, and reducing the impedance of the battery; since the PU in Example 9 has a smaller molecular weight than that in Example 1, it affects the combination effect of PU and the electrolyte. When the solvation is insufficient, it will lead to a large impedance of the battery cell and reduced cycle performance.
[0151] Furthermore, by observing the test results of Example 1, Example 7, Example 8, Comparative Example 5 and Comparative Example 6 in Table 1, it can be seen that the single-layer coating thickness of the PU slurry, that is, the depth of the groove constructed by the subsequent dissolution is too large or too small, which will affect the liquid retention consistency of the battery; when the single-layer coating thickness of the PU slurry is less than 1 / 10 of the total thickness of the coating layer of the negative electrode plate, the height of the constructed groove also decreases, which increases the migration path of Li+ and the liquid retention consistency of the battery and reduces the battery performance; when the single-layer coating thickness of the PU slurry is greater than 3 / 10 of the total thickness of the coating layer of the negative electrode plate, the height of the constructed groove also increases. Under the rolling process of the electrode plate, the groove is easily damaged by extrusion, resulting in an incomplete groove structure, thereby affecting the liquid retention consistency of the battery and reducing the battery performance.
[0152] Further, observing the test results of Example 1, Example 4, Example 5, Example 9 and Example 10 in Table 3, Example 1 has a 4≤(S / M)*10 higher than that of Example 4 and Example 10. 7 ≤67 is larger, which is mainly because the coating cross-sectional area of the PU slurry in Example 4 is smaller than that in Example 1, and the groove space is insufficient, resulting in reduced consistency of battery liquid retention; the molecular weight of PU in Example 10 is larger than that in Example 1, which aggravates the difficulty of dissolving the electrolyte and may cause polymer residue in the groove, resulting in reduced consistency of battery liquid retention.
[0153] Observing the test results of Example 1, Comparative Example 3, Comparative Example 4, Comparative Example 7 and Comparative Example 8 in Table 1 and Table 3, it can be seen that the (S / M)*10 of Comparative Example 3, Comparative Example 4, Comparative Example 7 and Comparative Example 8 is 7 The value of is not within the required range of 4 to 76. This is because in Comparative Examples 3 and 4, the coating cross-sectional area of the PU slurry is too high or too low, and does not fall within the 0.01 mm2 required in this solution. 2 ~0.1mm 2 In Comparative Examples 7 and 8, the molecular weight of PU in the polymer slurry is too high or too low, and does not fall within the range of 3000 to 50000 proposed in this solution; it directly affects the integrity of the grooves, affects the consistency of the battery's liquid retention, and thus affects the battery performance.
[0154] The above are only partial or preferred embodiments of the present invention. Neither the text nor the drawings can limit the scope of protection of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the overall concept of the present invention, or direct / indirect application in other related technical fields are included in the scope of protection of the present invention.
Claims
1. A multi-layer negative electrode sheet, characterized in that: It includes a negative electrode current collector and a first active layer, a composite layer and a second active layer sequentially stacked on one side of the negative electrode current collector; the composite layer includes a soluble polymer material layer obtained by a multi-striped coating method, and a third active layer filling the gaps in the soluble polymer material layer.
2. The multi-layer structured negative electrode sheet according to claim 1, characterized in that: The slurry used in the soluble polymer material layer includes any one of waterborne polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; the polymer used in the soluble polymer material layer has a molecular weight of 3000 to 50000, and / or a melting point of 50°C to 80°C.
3. The multi-layer negative electrode sheet according to claim 2, characterized in that: The composite layer is arranged in multiple layers; each of the composite layers covers the outer surface of the first active layer or the second active layer, and the outer surface of each of the composite layers is covered with the second active layer; the thickness of the soluble polymer material layer is 1 / 10 to 3 / 10 of the total thickness of the coating layer of the multi-layer structure negative electrode sheet.
4. The multi-layer negative electrode sheet according to claim 2 or 3, characterized in that: In the multi-striped coating method, the coating spacing is 0.5 mm to 5 mm, and / or 0.01 mm. 2 ~0.1mm 2 The soluble polymer material layer is applied on a coating cross-sectional area of 5. The multi-layer negative electrode sheet according to claim 4, characterized in that: The soluble polymer material layer is coated at a coating interval of 0.5 mm to 3 mm.
6. The multi-layer negative electrode sheet according to claim 5, characterized in that: The coating cross-sectional area of the soluble polymer material layer is denoted as S, the molecular weight of the polymer used in the soluble polymer material layer is denoted as M, 4≤(S / M)*10 7 ≤67.
7. A method for preparing a multi-layer structured negative electrode sheet, characterized in that: The steps include: S1, coating the negative electrode slurry on the surface of the negative electrode current collector and curing it to form a first active layer; S2, coating the surface of the first active layer with negative electrode slurry and polymer slurry and curing to obtain a composite layer; in the composite layer, the negative electrode slurry and the polymer slurry are both obtained by multi-striped coating; the polymer slurry forms a soluble polymer material layer, and the negative electrode slurry forms a third active layer to fill the gaps in the soluble polymer material layer; S3, coating the negative electrode slurry on the surface of the composite layer and curing it to form a second active layer.
8. The method for preparing a multi-layered negative electrode sheet according to claim 7, characterized in that: The step S2 comprises: Coating the polymer slurry on the surface of the first active layer by multi-striped coating and curing to form the soluble polymer material layer; Applying negative electrode slurry in the gaps of the soluble polymer material layer to fill and solidify to obtain a third active layer, wherein the soluble polymer material layer and the third active layer form the composite layer; or; Coating the negative electrode slurry on the surface of the first active layer by a multi-striped coating method and curing the negative electrode slurry to obtain the third active layer; Applying the polymer slurry in the gaps of the third active layer to fill and solidify to obtain the soluble polymer material layer, wherein the soluble polymer material layer and the third active layer form the composite layer; or; The polymer slurry and the negative electrode slurry are coated with multiple stripes by using a double die head at the same time and then cured to obtain the composite layer.
9. The method for preparing a multi-layered negative electrode sheet according to claim 8, characterized in that: The polymer slurry is any one of waterborne polyurethane, polyethylene oxide, polyacrylonitrile, polymethyl methacrylate, and polyvinylidene fluoride; the polymer used in the polymer slurry has a molecular weight of 3000 to 50000, and / or a melting point of 50°C to 80°C.
10. The method for preparing a multi-layered negative electrode sheet according to claim 8 or 9, characterized in that: The step S2 further comprises: The cross-sectional area of 0.01 mm is intermittently coated on the surface of the pole piece in a multi-strip coating manner according to a coating interval of 0.5 mm to 5 mm. 2 ~0.1mm 2 A layer of dissolvable polymer material.
11. The method for preparing a multi-layered negative electrode sheet according to claim 10, characterized in that: The mass concentration of the polymer slurry is 10 mg / ml to 50 mg / ml.
12. The method for preparing a multi-layer structured negative electrode sheet according to any one of claims 7 to 11, characterized in that: Also includes: S4, repeating the operations in steps S2 and S3 to obtain the multi-layer structured negative electrode sheet; In the multi-layer structured negative electrode sheet, the thickness of the soluble polymer material layer is 1 / 10 to 3 / 10 of the total thickness of the coating layers of the multi-layer structured negative electrode sheet.
13. The method for preparing a multi-layered negative electrode sheet according to claim 8, characterized in that: The curing is ultraviolet light curing or drying curing; During the UV curing, the intensity of the UV light is 900 mW / cm 2 ~1100mW / cm 2 , and / or the curing power is 30% to 50%, and / or the curing time is 5s to 15s; During the drying and curing, the negative electrode current collector is dried in an oven at 40° C. to 50° C.
14. A lithium ion battery, characterized in that: A multilayer negative electrode sheet according to any one of claims 1 to 6, further comprising a positive electrode sheet, a separator and an electrolyte; The electrolyte includes a lithium salt and an organic solvent; wherein the organic solvent includes at least one of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate.
